Evaluation of the knowledge and attitudes of pregnant women undergoing preoperative assessment in the anesthesia clinic regarding Monkeypox virus disease in Turkey - Oğuz Kağan Bulut; Sevim Şenol Karataş; Sait Fatih Öner (BMC Pregnancy and Childbirth)
Abstract Objective This study aims to evaluate the knowledge and attitudes of pregnant women undergoing preoperative assessment in the anesthesia clinic regarding monkeypox virus disease and related vaccines. Methods This descriptive and cross-sectional study was conducted between November 2024 and March 2025 at the Anesthesia Clinic of Elazığ Fethi Sekin City Hospital among pregnant women who applied for preoperative evaluation. Pregnant women aged 18 years and older who agreed to participate were included in the study, provided they completed the survey. The survey was administered face-to-face. The sample size for the study was calculated using the recommended formula for small populations, resulting in a required sample of 208 participants. The survey was developed based on studies related to COVID-19 (coronavirus disease 2019) and monkeypox. It consisted of four sections: sociodemographic data, knowledge test, attitude toward the disease, and attitude toward vaccination. A validated questionnaire with acceptable reliability (Cronbach alpha = 0.82) was used to assess knowledge and attitudes. Results A total of 300 pregnant women who applied to the anesthesia clinic were included in the study. The mean age of the participants was 30.62 ± 6.62 years, with 77 (25.66%) having completed high school or university education, and 86 (28.66%) experiencing their first pregnancy. The participants’ mean knowledge score was 9.5 ± 2.46, and 114 (38%) demonstrated a good level of knowledge. Additionally, 168 (56%) had a positive attitude toward monkeypox virus, but only 28 (9.33%) expressed willingness to receive the vaccine. Conclusion The findings of this study indicate that while pregnant women demonstrate moderate knowledge and relatively positive attitudes toward monkeypox, their willingness to receive vaccination remains low. Tailored educational and counseling interventions are essential to improve awareness and vaccine acceptance in this vulnerable population.